Micro-nano corrugated polymer film, preparation method and application thereof
Patent Information
- Application Number
- CN202610964731.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-09
AI Technical Summary
[0006]为了解决现有技术中微纳褶皱制备依赖基底预应变、无法适用于刚性基底和复杂三维形状基底、部分方法需要溶液法制备底层而不适用于对溶剂敏感材料的问题
现有制备微纳褶皱的技术可通过在沉积于柔性聚合物基底上的薄膜中引入应变,可制备出褶皱结构。一种代表性策略是先将弹性体基底进行热膨胀或机械预拉伸,然后在其上沉积一层坚硬的薄膜。随后通过冷却或释放应变,在上层薄膜中产生压应力并引发褶皱形成。此外,热收缩聚合物基底,包括聚苯乙烯和聚烯烃,也被用来通过热收缩诱导上层薄膜产生压缩。尽管取得了这些进展,褶皱的形成仍然依赖于基底的变形,从而限制了其在刚性基底上的应用,并阻碍了其在结构复杂的三维支撑体上的集成。
Smart Images

Figure CN122875447A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of polymer film preparation technology, and in particular to a micro / nano wrinkled polymer film, its preparation method and application. Background Technology
[0002] Currently, micro- and nano-scale surface structures play a crucial role in regulating the interfacial behavior of materials, including wettability, adhesion, frosting and icing behavior, and biological interactions. These behaviors determine the functional performance of materials in environmental, energy, and biomedical applications. Micro- and nano-folds, as a representative surface structure morphology, originate from stress-driven mechanical instability in layered materials. When the compressive stress accumulated in a film constrained by in-plane exceeds a critical stability threshold, the planar state becomes energy-unfavorable, thus releasing stress through out-of-plane deformation, forming a folded structure.
[0003] Existing techniques for fabricating micro / nano wrinkles typically rely on the deformation of an elastic substrate to achieve wrinkle formation. A representative strategy involves first thermally expanding or mechanically pre-stretching an elastomer substrate, then depositing a rigid thin film on it. Subsequently, cooling or releasing the strain generates compressive stress in the upper film, inducing wrinkle formation. Additionally, heat-shrinkable polymer substrates, including polystyrene and polyolefins, have also been used to induce compression in the upper film through thermal shrinkage. These methods can successfully fabricate wrinkled structures on flexible substrates, but the wrinkle formation depends on substrate deformation, thus limiting their application on rigid substrates and hindering their integration into complex three-dimensional supports.
[0004] Furthermore, these methods are not entirely gas-phase processes; their underlying processes require solution-based preparation, such as spin coating. Therefore, they are not well-suited for substrates with complex geometries and may be incompatible with solvent-sensitive materials, thus limiting their application scenarios.
[0005] Therefore, there is a need for a method to prepare micro-nano wrinkles that does not require substrate deformation, is solvent-free, and is applicable to various substrate materials and complex shapes, in order to expand the application scope of micro-nano structure surface engineering. Summary of the Invention
[0006] To address the problems in existing technologies where the fabrication of micro-nano folds relies on substrate pre-straining, is not applicable to rigid substrates and complex three-dimensional shaped substrates, and requires solution-based preparation of the bottom layer which is not suitable for solvent-sensitive materials.
[0007] This application provides a method and application for preparing micro / nano-folds using initiated chemical vapor deposition (iCVD). This iCVD method is a simple, efficient, and mild polymer chemical vapor deposition technique. This application achieves spontaneous formation of micro / nano-folds through solvent-free, sequential iCVD deposition of poly(2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane) (PV3D3) and poly(1H,1H,2H,2H-perfluorodecyl acrylate) (PPFDA). Due to the inconsistency in elastic modulus between the PV3D3 and PPFDA layers, intrinsic stress is generated during growth, thus enabling spontaneous formation of micro / nano-folds without strain or an elastic substrate. The conformal and solvent-free nature of iCVD allows the folded structure to be directly integrated onto substrates of varying rigidity and complex shapes. The resulting micro / nano-folded coating exhibits durable hydrophobic and antifouling properties, delayed frosting and icing, and reduced bacterial adhesion, making it applicable to the surface modification of antifouling, anti-frost, anti-icing, and antibacterial materials.
[0008] To further prepare polymer micro / nano wrinkles, this application adopts the following technical solution: In a first aspect, embodiments of this application provide a method for preparing micro / nano-wrinkled thin films by initiation-based chemical vapor deposition, comprising: placing a substrate on a sample stage of a chemical vapor deposition reactor; vaporizing an initiator and a first monomer by heating and allowing them to flow into the reactor, wherein the initiator decomposes upon heating to generate free radicals, initiating a free radical polymerization reaction of the first monomer, thereby depositing a first polymer layer on the surface of the substrate; stopping the flow of the first monomer, and vaporizing the initiator and a second monomer by heating and allowing them to flow into the reactor, wherein the initiator decomposes upon heating to generate free radicals, initiating a free radical polymerization reaction of the second monomer, thereby depositing a second polymer layer on the surface of the first polymer layer; wherein the difference in elastic modulus between the first polymer layer and the second polymer layer generates compressive stress during film growth, spontaneously forming a micro / nano-wrinkled structure.
[0009] In some embodiments, the first monomer is 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, the first polymer layer is poly(2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane); the second monomer is 1H,1H,2H,2H-perfluorodecyl acrylate, and the second polymer layer is poly(1H,1H,2H,2H-perfluorodecyl acrylate).
[0010] In some embodiments, the thickness of the first polymer layer is 50 nm to 1000 nm.
[0011] In some embodiments, the initiator is di-tert-butyl peroxide, which is decomposed by heating with a nickel-chromium wire to generate free radicals.
[0012] In some embodiments, the heating temperature of the nichrome wire is 200°C to 400°C.
[0013] In some embodiments, the temperature of the substrate during deposition is 30°C to 60°C.
[0014] In some embodiments, the deposition reaction time of the second polymer layer is 1 to 20 minutes.
[0015] In some embodiments, the pressure of the reactor is 13.3 Pa to 133.3 Pa (0.1 Torr to 1.0 Torr).
[0016] In some embodiments, the substrate is a rigid substrate or a substrate with a complex three-dimensional shape.
[0017] In some embodiments, the thickness of the first polymer layer is monitored by a real-time laser interferometer, and the inflow of the first monomer is stopped when the thickness reaches a predetermined value.
[0018] In some embodiments, the resulting film has a water contact angle greater than 150°.
[0019] In some embodiments, the micro-nano folded structure has a worm-like or labyrinth-like morphology.
[0020] In some embodiments, the substrate is selected from at least one of glass, plastic, fabric, and silicon wafer.
[0021] The preparation method provided in this application embodiment enables the formation of micro-nano wrinkled structures on rigid substrates and complex three-dimensional shaped substrates without substrate pre-strain. The all-gas phase process eliminates the need for solvents, avoiding the influence of solution methods on sensitive materials. The process is simple, the reaction conditions are mild, and the prepared thin film has a water contact angle of over 150° and exhibits superhydrophobic properties.
[0022] Secondly, embodiments of this application provide a micro / nano-wrinkled film, comprising: a first polymer layer, wherein the first polymer layer is poly2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane; a second polymer layer, wherein the second polymer layer is poly1H,1H,2H,2H-perfluorodecyl acrylate; the first polymer layer and the second polymer layer are grafted to form P(V3D3- g -PFDA) graft copolymer, the film surface exhibits micro-nano wrinkled morphology.
[0023] In some embodiments, the thickness of the first polymer layer is 50 nm to 1000 nm.
[0024] In some embodiments, the water contact angle of the film is greater than 150°.
[0025] In some embodiments, the micro-nano fold morphology is a worm-like or labyrinth-like structure.
[0026] In some embodiments, the thin film is deposited on at least one substrate selected from glass, plastic, fabric, and silicon wafer.
[0027] The micro-nano wrinkled film provided in this application embodiment spontaneously forms micro-nano wrinkles through the difference in elastic modulus of the bilayer graft copolymer structure, without relying on a specific substrate type. The film surface exhibits a worm-like or labyrinthine micro-nano wrinkle morphology, with a water contact angle greater than 150°, and has superhydrophobic properties.
[0028] Thirdly, embodiments of this application provide the application of the micro / nano-wrinkled film prepared by the method described in the first aspect in antifouling.
[0029] In some embodiments, the antifouling application is for antifouling of architectural glass surfaces.
[0030] In some embodiments, the antifouling application is a stain-resistant application for textile surfaces.
[0031] The antifouling application provided in this application utilizes the air cushion effect and low surface energy characteristics generated by the micro-nano pleated structure, making it difficult for various liquid pollutants such as water, soy sauce, milk, coffee, and cola to spread in a near-spherical droplet shape on the film surface. Solid pollutants are easily carried away by water flow without residue, thus achieving excellent self-cleaning function.
[0032] Fourthly, embodiments of this application provide the application of the micro / nano-wrinkled film prepared by the method described in the first aspect in anti-frost and anti-icing.
[0033] In some embodiments, the application is for surface anti-icing of aerospace equipment.
[0034] The anti-frost and anti-icing application provided in this application utilizes superhydrophobic micro-nano structures to reduce the actual contact area between water droplets and the surface, significantly delaying the condensation and freezing process of water on the surface. Anti-icing is achieved through a physical mechanism, without the need for chemical anti-icing agents or external energy.
[0035] Fifthly, embodiments of this application provide the application of the micro / nano-wrinkled film prepared by the method described in the first aspect in antibacterial applications.
[0036] In some embodiments, the antimicrobial application is antimicrobial treatment of medical device surfaces.
[0037] In some embodiments, the antibacterial target is Escherichia coli.
[0038] The antibacterial application provided in the embodiments of this application utilizes micro-nano wrinkled structures to reduce the effective contact sites between bacteria and the surface. Compared with polystyrene plastic sheets and PV3D3 coated surfaces, P(V3D3- g-PFDA) significantly reduces the amount of E. coli adhering to its surface, achieving antibacterial activity through a physical mechanism without the need for chemical antibacterial agents, thus avoiding drug resistance issues.
[0039] It is understood that the beneficial effects of the second to fifth aspects mentioned above can be found in the relevant descriptions in the first aspect mentioned above, and will not be repeated here.
[0040] In addition, this application provides a method for preparing micro / nano wrinkles using polymer chemical vapor deposition technology, comprising: The substrate (glass slide, plastic sheet, cloth, silicon wafer, etc.) is placed on the sample stage of the chemical vapor deposition reactor; nickel-chromium wires are arranged above the reactor stage and heated to a predetermined temperature; The initiator di-tert-butyl peroxide and the first functional monomer 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane (V3D3) are heated to vaporize and then flow into the reactor. The initiator enters the reactor and is decomposed by heating with a nickel-chromium wire to generate free radicals, which in turn initiate a free radical chain polymerization reaction between monomers to form PV3D3. When the film reaches the required thickness, V3D3 and TBP are turned off, and the second functional monomer 1H,1H,2H,2H-perfluorodecyl acrylate (PFDA) and TBP are turned on. The reaction is stopped when the required time has elapsed.
[0041] As a further improvement of this application, the initiator di-tert-butyl peroxide, the first functional monomer V3D3, and the second functional monomer PFDA are heated to (10-30)°C, (40-70)°C, and (60-90)°C, respectively.
[0042] As a further improvement of this application, the thickness of the first layer PV3D3 film is not less than (50-1000) nm, and the initiator and monomer flow is stopped when the monitored film thickness reaches the expected requirement.
[0043] As a further improvement to this application, the PFDA reaction time for the second layer film is 1-20 minutes.
[0044] As a further improvement to this application, the substrate is a glass sheet, a plastic sheet, a fabric, a silicon wafer, etc.
[0045] As a further improvement of this application, during the process of depositing the synthesized polymer on the substrate material to form a thin film, the substrate temperature is controlled by a water circulation system and monitored by a thermocouple, so that the temperature does not exceed the tolerance temperature of the substrate material.
[0046] As a further improvement of this application, the nickel-chromium wires are arranged 2.5 cm to 3 cm above the reaction platform, and the nickel-chromium wires are heated to 200-400°C.
[0047] As a further improvement of this application, the pressure of the reactor is controlled at 0.1-1.0 Torr by a throttling valve, and the flow rate of each monomer participating in the reaction is controlled by a mass flow controller.
[0048] As a further improvement of this application, the film thickness is monitored in real time by a laser interferometer during the deposition of the synthesized polymer on the substrate material to form a thin film.
[0049] As a further improvement to this application, the thin film is P(V3D3- g -PFDA).
[0050] Compared with the prior art, this application has the following technical effects and advantages: Existing techniques for fabricating micro / nano wrinkles can create wrinkled structures by introducing strain into a thin film deposited on a flexible polymer substrate. A representative strategy involves first thermally expanding or mechanically pre-stretching the elastomeric substrate, and then depositing a rigid thin film on top. Subsequently, cooling or releasing the strain generates compressive stress in the upper film, inducing wrinkle formation. Furthermore, heat-shrinkable polymer substrates, including polystyrene and polyolefins, have also been used to induce compression in the upper film through thermal shrinkage. Despite these advances, wrinkle formation still depends on substrate deformation, limiting its application on rigid substrates and hindering its integration into complex three-dimensional supports.
[0051] Even without substrate deformation, differences in mechanical properties between adjacent material layers can induce wrinkle formation. When cross-linked PFDA films are deposited on a relatively soft underlying layer via initiated chemical vapor deposition (iCVD), elastic mismatch generates the driving force for wrinkle formation. Studies have shown that the degree of wrinkling can be easily adjusted by regulating the cross-linking density of the iCVD deposited layer and thus its rigidity. However, these methods of achieving wrinkles using iCVD are not entirely vapor-phase processes; their underlying layers require solution-based preparation (such as spin coating), making them less suitable for substrates with complex geometries and potentially incompatible with solvent-sensitive materials.
[0052] This application presents a substrate-independent bilayer strategy for forming micro / nano wrinkles through solvent-free, sequential iCVD deposition of poly(1,3,5-trimethyl-1,3,5-trivinylcyclotrisiloxane) and poly(1H,1H,2H,2H-perfluorodecyl acrylate). The elastic mismatch between the lower and upper layers of the vapor-deposited layer intrinsically generates compressive stress during growth, thus spontaneously forming micro / nano wrinkles without pre-straining or an elastic substrate. The conformal and solvent-free nature of iCVD allows the wrinkled structures to be directly integrated onto substrates of varying rigidity and complex shapes. The resulting micro / nano wrinkled coating exhibits superhydrophobic, antifouling, antimicrobial adhesion, and anti-frost / anti-icing properties. This iCVD method for preparing micro / nano wrinkles represents a substrate-independent approach to micro / nano structure surface engineering. Attached Figure Description
[0053] Figure 1 This is a schematic diagram of this application; Figure 2 This is the iCVD thin film P(V3D3- in Embodiment 1 of this application. g SEM image of -PFDA); Figure 3 In Embodiment 1 of this application, P(V3D3- g -PFDA) water contact angle diagram; Figure 4 In Embodiment 1 of this application, P(V3D3- g -PFDA) anti-fouling effect diagram; Figure 5 In Embodiment 1 of this application, P(V3D3- g SEM image of PFDA antimicrobial adhesion; Figure 6 In Embodiment 1 of this application, P(V3D3- g -PFDA) Effect diagram of anti-frost and anti-icing properties. Detailed Implementation
[0054] To make the objectives, technical solutions, and advantages of this application clearer, the embodiments of this application will be described in detail below with reference to the accompanying drawings. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be arbitrarily combined with each other.
[0055] Many specific details are set forth in the following description in order to provide a full understanding of this application. However, this application may also be implemented in other ways different from those described herein. Therefore, the scope of protection of this application is not limited to the specific embodiments disclosed below.
[0056] Initiated chemical vapor deposition (iCVD) is a novel, green method for preparing functional polymer thin films. It combines traditional liquid-phase free radical polymerization with chemical vapor deposition technology, enabling monomers to generate polymer thin films through free radical polymerization under mild reaction conditions. The film thickness is precisely controlled by laser monitoring during the deposition process, allowing for the uniform deposition of films ranging from tens of micrometers to several micrometers onto substrates of various shapes and materials.
[0057] This application describes the synthesis of P(V3D3-) on glass sheets, plastic sheets, fabrics, silicon wafers, etc., using iCVD. g -PFDA) thin films can be prepared to create superhydrophobic films with micro-nano structures, which have important application prospects in fields such as antifouling, antibacterial adhesion, anti-frost and anti-icing.
[0058] like Figure 1 As shown, the initiation-based chemical vapor deposition method provided in this application sequentially deposits a bilayer structure of poly(2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane) and poly(1H,1H,2H,2H-perfluorodecyl acrylate). Utilizing the difference in elastic modulus between the two layers, stress is intrinsically generated during growth, thus spontaneously forming micro / nano wrinkles without pre-strain or an elastic substrate. This method employs solvent-free vapor deposition, possesses conformal characteristics, and can be directly integrated onto substrates of varying rigidity and complex shapes.
[0059] The first objective of this application is to provide a method for preparing micro / nano wrinkles using polymer chemical vapor deposition technology, comprising the following steps: Materials such as glass sheets, plastic sheets, cloth, and silicon wafers are placed on the sample stage of a polymer chemical vapor deposition reactor.
[0060] The initiator di-tert-butyl peroxide (TBP) and the first functional monomer 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane (V3D3) were heated to (10-30) °C and (40-70) °C, respectively, to vaporize before flowing into the reactor; the flow rates of each monomer were controlled by a mass flow controller. Nichrome wires were neatly arranged 2.5-3 cm above the reaction platform and heated to 200-400 °C.
[0061] The initiator TBP enters the reactor and decomposes upon heating with a nickel-chromium wire to generate free radicals, which then initiate a free radical chain polymerization reaction. The synthesized polymer is deposited on the substrate material and the control silicon wafer. During deposition, the substrate temperature is controlled by a water circulation system and monitored by thermocouples at 30-60°C to ensure that the performance of the substrate material is not damaged. The reactor pressure is controlled at 0.1-1.0 Torr by a throttling valve. The film thickness is controlled at 50 nm-1000 nm by real-time monitoring with a laser interferometer. When the PV3D3 coating thickness reaches the expected requirement, the monomers V3D3 and TBP stop flowing in, and the second functional monomer 1H,1H,2H,2H-perfluorodecyl acrylate (PFDA) and TBP are activated. The reaction is stopped when the required time is reached.
[0062] The PV3D3 is 50 nm-1000 nm.
[0063] The initiator TBP and the second functional monomer PFDA are heated to (10-30) °C and (60-90) °C respectively to vaporize them before flowing into the reactor; the flow rate of each monomer is controlled by a mass flow controller. Nichromium wires are neatly arranged 2.5-3 cm above the reaction platform and heated to 200-400 °C.
[0064] The PPFDA reaction takes 1-20 minutes.
[0065] This application describes a gas-phase iCVD method for preparing a polymer film with a micro-nano wrinkled structure by grafting 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane (V3D3) and 1H,1H,2H,2H-perfluorodecyl acrylate (PFDA) in a bilayer manner.
[0066] In addition, the micro-nano folds prepared in this application can be applied to the surface of various objects, giving them properties such as anti-fouling, antibacterial adhesion, anti-frost and anti-icing.
[0067] The present application will be further described in detail below with reference to specific embodiments and accompanying drawings.
[0068] Example 1 P(V3D3- g Preparation of PFDA: Using glass, quartz, fabric, or silicon wafers as substrates, samples were placed on the stage of a polymer chemical vapor deposition reactor. The initiator di-tert-butyl peroxide (TBP) and the first functional monomer 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane (V3D3) were heated to 25°C and 50°C, respectively, and then vaporized and flowed into the reactor. Nichrome wires were neatly arranged 2.5 cm above the reactor stage and heated to 240°C. The initiator TBP entered the reactor and decomposed upon heating with the nichrome wires, generating free radicals that then initiated a free radical chain polymerization reaction. The synthesized PV3D3 was deposited on glass, quartz, fabric, and control silicon wafers. During deposition, the substrate temperature was controlled by a water circulation system and monitored at 38°C by thermocouples. The reactor pressure was controlled at 0.5 Torr by a throttling valve. The film thickness was monitored using a real-time laser interferometer; when the PV3D3 coating thickness reached 200 nm, the flow of monomer V3D3 stopped. Open the second functional monomer 1H,1H,2H,2H-perfluorodecyl acrylate (PFDA), heat it to 75°C and vaporize it into the reaction chamber. Stop the reaction after 6 minutes.
[0069] in, Figure 2 and Figure 3 The substrate is a silicon wafer. Figure 4 It's glass. Figure 5 It's a plastic sheet. Figure 6 It is quartz.
[0070] Example 2 P(V3D3- g Preparation of PFDA: Glass, quartz, and silicon wafers were placed on the sample stage of a polymer chemical vapor deposition reactor. The initiator di-tert-butyl peroxide (TBP) and the first functional monomer 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane (V3D3) were heated to 30°C and 40°C, respectively, and then vaporized and flowed into the reactor. Nichrome wires were neatly arranged 2.5 cm above the reactor stage and heated to 200°C. The initiator TBP entered the reactor and decomposed upon heating with the nichrome wires, generating free radicals that then initiated a free radical chain polymerization reaction. The synthesized PV3D3 was deposited on the glass, quartz, fabric, and control silicon wafers. During deposition, the substrate temperature was controlled by a water circulation system and monitored at 30°C by thermocouples. The reactor pressure was controlled at 0.1 Torr by a throttling valve. The film thickness was monitored using a real-time laser interferometer; when the PV3D3 coating thickness reached 50 nm, the flow of monomer V3D3 stopped. Open the second functional monomer 1H,1H,2H,2H-perfluorodecyl acrylate (PFDA), heat it to 90°C and vaporize it into the reaction chamber. Stop the reaction after 1 minute.
[0071] Example 3 P(V3D3- gPreparation of PFDA: Glass, quartz, and silicon wafers were placed on the sample stage of a polymer chemical vapor deposition reactor. The initiator di-tert-butyl peroxide (TBP) and the first functional monomer 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane (V3D3) were heated to 10°C and 70°C, respectively, and then vaporized and flowed into the reactor. Nichrome wires were neatly arranged 3 cm above the reactor stage and heated to 400°C. The initiator TBP entered the reactor and decomposed upon heating with the nichrome wires, generating free radicals that then initiated a free radical chain polymerization reaction. The synthesized PV3D3 was deposited on the glass, quartz, fabric, and control silicon wafers. During deposition, the substrate temperature was controlled by a water circulation system and monitored at 30°C by thermocouples. The reactor pressure was controlled at 1 Torr by a throttling valve. The film thickness was monitored using a real-time laser interferometer; when the PV3D3 coating thickness reached 300 nm, the flow of monomer V3D3 stopped. Open the second functional monomer 1H,1H,2H,2H-perfluorodecyl acrylate (PFDA), heat it to 60°C and vaporize it into the reaction chamber. Stop the reaction after 20 minutes.
[0072] like Figure 2 As shown, this is the iCVD thin film P(V3D3-) in Embodiment 1 of this application. g SEM image of P(V3D3-g-PFDA). Obvious micro- and nano-folds are observed on both the surface and sides of the film. The P(V3D3-g-PFDA) film prepared in Example 1 was characterized using scanning electron microscopy. Figure 2 It can be seen that the surface and sides of the film exhibit obvious micro-nano wrinkled structures, with worm-like or labyrinthine morphologies. This micro-nano wrinkled structure originates from the difference in elastic modulus between the poly(2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane) bottom layer and the poly(1H,1H,2H,2H-perfluorodecyl acrylate) top layer, which spontaneously forms due to compressive stress generated during the deposition process.
[0073] like Figure 3 As shown, the water contact angle of the P(V3D3-g-PFDA) film prepared in Example 1 was tested. From... Figure 3 As can be seen, the water contact angle of the P(V3D3-g-PFDA) film exceeds 150°, exhibiting superhydrophobic properties. This superhydrophobic performance originates from the synergistic effect of the micro / nano-wrinkled structure and the low surface energy poly(1H,1H,2H,2H-perfluorodecyl acrylate).
[0074] like Figure 4 As shown, this is P(V3D3-) in Embodiment 1 of this application. g -PFDA) anti-fouling effect diagram. Figure 4 a indicates that various liquid contaminants are present in P(V3D3- g-PFDA) coating does not easily spread on glass. Figure 4 b indicates that flowing water can carry away P(V3D3- g -PFDA) dye contaminants on coated glass surfaces Figure 4 c indicates that the blue polluting liquid is not in P(V3D3- g -PFDA) coating residue on glass surface indicates P(V3D3- g -PFDA) coating gives the glass surface excellent anti-fouling properties, which is due to the synergistic effect of micro-nano wrinkled structure and superhydrophobic properties.
[0075] like Figure 5 As shown, this is P(V3D3-) in Embodiment 1 of this application. g SEM images of antimicrobial adhesion of P(V3D3-) coatings. Compared with the surfaces of polystyrene sheets (PS) and PV3D3 coated with P(V3D3-) coatings. g The adhesion of *P(V3D3-g-PFDA)* significantly reduced that of *E. coli*, indicating its antibacterial adhesion effect. *E. coli* was incubated on polystyrene sheets, poly(2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane) (PV3D3) coated surfaces, and P(V3D3-g-PFDA) coated surfaces, respectively. Bacterial adhesion was observed using scanning electron microscopy after incubation. Figure 5 It can be seen that the number of E. coli adhering to the P(V3D3-g-PFDA) coating surface is significantly reduced compared to the polystyrene plastic sheet and the PV3D3 coated surface. This indicates that the P(V3D3-g-PFDA) coating has an antibacterial adhesion effect, and the micro-nano wrinkled structure reduces bacterial adhesion through physical means.
[0076] like Figure 6 As shown, this is P(V3D3-) in Embodiment 1 of this application. g The anti-frost and anti-icing effects of the P(V3D3-) coating are shown in the image. Compared to the control quartz plate, the P(V3D3-) coating... g P(V3D3-g-PFDA) significantly slows down the frosting and freezing process of water on the surface of quartz sheets. The anti-frost and anti-icing performance of the P(V3D3-g-PFDA) coated quartz sheets prepared in Example 1 were tested. Coated and uncoated quartz sheets were placed in the same low-temperature, high-humidity environment, and the frosting and freezing process was observed. Figure 6 It can be seen that, compared with the uncoated quartz sheet, the P(V3D3-g-PFDA) coated quartz sheet significantly slows down the frosting and freezing process of water on the surface. This indicates that the P(V3D3-g-PFDA) coating has the property of delaying frosting and freezing, which is due to the fact that the superhydrophobic surface reduces the contact area and contact time between water droplets and the film surface.
[0077] Examples 2-3 have verified that the water contact angle of the thin film prepared in this application exceeds 150°, and it has the functions of superhydrophobicity, antifouling, antibacterial adhesion, and anti-frost and anti-icing.
[0078] This method employs initiation-based chemical vapor deposition (CVD) technology, sequentially depositing a poly(2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane) underlayer and a poly(1H,1H,2H,2H-perfluorodecyl acrylate) overlayer. The difference in elastic modulus between the two layers spontaneously forms micro / nano-folded structures during film growth. This method requires no substrate pre-straining, uses an all-vapor phase process without solvents, and is applicable to rigid substrates and complex three-dimensional shapes. The prepared films have a water contact angle exceeding 150° and exhibit superhydrophobic, antifouling, antibacterial adhesion, and anti-frost / anti-icing properties, making them suitable for applications in architectural glass, textiles, medical devices, aerospace equipment, and other fields.
[0079] Example 4 P(V3D3- g Preparation of PFDA: Glass, quartz, fabric, and silicon wafers were placed on the sample stage of a polymer chemical vapor deposition reactor. The initiator di-tert-butyl peroxide (TBP) and the first functional monomer 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane (V3D3) were heated to 10°C and 40°C, respectively, and then vaporized and flowed into the reactor. Nichrome wires were neatly arranged 3 cm above the reactor stage and heated to 200°C. The initiator TBP entered the reactor and decomposed upon heating with the nichrome wires, generating free radicals that then initiated a free radical chain polymerization reaction. The synthesized PV3D3 was deposited on the glass, quartz, fabric, and control silicon wafers. During deposition, the substrate temperature was controlled by a water circulation system and monitored at 30°C by thermocouples. The reactor pressure was controlled at 0.1 Torr by a throttling valve. The film thickness was monitored using a real-time laser interferometer; when the PV3D3 coating thickness reached 50 nm, the flow of monomer V3D3 stopped. Open the second functional monomer 1H,1H,2H,2H-perfluorodecyl acrylate (PFDA), heat it to 70°C and vaporize it into the reaction chamber. Stop the reaction after 6 minutes.
[0080] Example 5 P(V3D3- g Preparation of PFDA: Glass, quartz, and silicon wafers were placed on the sample stage of a polymer chemical vapor deposition reactor. The initiator di-tert-butyl peroxide (TBP) and the first functional monomer 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane (V3D3) were heated to 30°C and 70°C, respectively, and then vaporized and flowed into the reactor. Nichrome wires were neatly arranged 2.6 cm above the reactor stage and heated to 400°C. The initiator TBP entered the reactor and decomposed upon heating with the nichrome wires, generating free radicals that then initiated a free radical chain polymerization reaction. The synthesized PV3D3 was deposited on the glass, quartz, fabric, and control silicon wafers. During deposition, the substrate temperature was controlled by a water circulation system and monitored at 60°C by thermocouples. The reactor pressure was controlled at 0.6 Torr by a throttling valve. The film thickness was monitored using a real-time laser interferometer; when the PV3D3 coating thickness reached 1000 nm, the flow of monomer V3D3 stopped. Open the second functional monomer 1H,1H,2H,2H-perfluorodecyl acrylate (PFDA), heat it to 80°C and vaporize it into the reaction chamber. Stop the reaction after 3 minutes.
[0081] Example 6 P(V3D3- g Preparation of PFDA: Glass, quartz, and silicon wafers were placed on the sample stage of a polymer chemical vapor deposition reactor. The initiator di-tert-butyl peroxide (TBP) and the first functional monomer 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane (V3D3) were heated to 20°C and 60°C, respectively, and then vaporized and flowed into the reactor. Nichrome wires were neatly arranged 3 cm above the reactor stage and heated to 350°C. The initiator TBP entered the reactor and decomposed upon heating with the nichrome wires, generating free radicals that then initiated a free radical chain polymerization reaction. The synthesized PV3D3 was deposited on the glass, quartz, fabric, and control silicon wafers. During deposition, the substrate temperature was controlled by a water circulation system and monitored at 50°C by thermocouples. The reactor pressure was controlled at 0.6 Torr by a throttling valve. The film thickness was monitored using a real-time laser interferometer; when the PV3D3 coating thickness reached 500 nm, the flow of monomer V3D3 stopped. Open the second functional monomer 1H,1H,2H,2H-perfluorodecyl acrylate (PFDA), heat it to 70°C and vaporize it into the reaction chamber. Stop the reaction after 10 minutes.
[0082] Examples 3-6 have verified that the thin films prepared in this application have a water contact angle of over 150° and possess superhydrophobic, antifouling, antibacterial adhesion, antifrost and anti-icing functions.
[0083] This application provides the application of the micro-nano wrinkled film prepared by the above method in antibacterial applications.
[0084] In some embodiments, the application is for surface anti-icing of aerospace equipment.
[0085] The anti-frost and anti-icing application provided in this application utilizes superhydrophobic micro-nano structures to reduce the actual contact area between water droplets and the surface, significantly delaying the condensation and freezing process of water on the surface. Anti-icing is achieved through a physical mechanism, without the need for chemical anti-icing agents or external energy.
[0086] Fifthly, embodiments of this application provide the application of the micro / nano-wrinkled film prepared by the method described in the first aspect in antibacterial applications.
[0087] In some embodiments, the antimicrobial application is antimicrobial treatment of medical device surfaces.
[0088] In some embodiments, the antibacterial target is Escherichia coli.
[0089] The antibacterial application provided in this application utilizes a micro-nano pleated structure to reduce the effective contact sites between bacteria and the surface. Compared with polystyrene plastic sheets and PV3D3 coated surfaces, the E. coli adhering to the P(V3D3-g-PFDA) surface is significantly reduced. Antibacterial action is achieved through a physical mechanism, eliminating the need for chemical antibacterial agents and avoiding drug resistance issues.
[0090] All articles and references disclosed above, including patent applications and publications, are incorporated herein by reference for various purposes. The term “substantially constitutes…” used to describe a combination should include the identified elements, components, parts, or steps, as well as other elements, components, parts, or steps that do not substantially affect the essential novelty of the combination. The use of the terms “comprising” or “including” to describe combinations of elements, components, parts, or steps herein also contemplates embodiments substantially constituted by such elements, components, parts, or steps. The use of the term “may” herein is intended to indicate that any described attribute included by “may” is optional.
[0091] Multiple elements, components, parts, or steps can be provided by a single integrated element, component, part, or step. Alternatively, a single integrated element, component, part, or step can be divided into multiple separate elements, components, parts, or steps. The use of "a" or "an" to describe an element, component, part, or step does not imply the exclusion of other elements, components, parts, or steps.
[0092] It should be understood that the above description is for illustrative purposes and not for limitation. Many embodiments and applications beyond the provided examples will be apparent to those skilled in the art upon reading the above description. Therefore, the scope of this teaching should not be determined by reference to the above description, but rather by reference to the foregoing claims and the full scope of their equivalents. For purposes of completeness, all articles and references, including patent applications and publications, are incorporated herein by reference. The omission of any aspect of the subject matter disclosed herein in the foregoing claims is not intended as a waiver of that subject matter, nor should it be construed as an indication that the applicant has not considered that subject matter as part of the disclosed inventive subject matter.
Claims
1. A method for preparing micro / nano-wrinkled thin films by initiation-based chemical vapor deposition, characterized in that, include: The substrate is placed on the sample stage of the chemical vapor deposition reactor; The initiator and the first monomer are vaporized by heating and then flow into the reactor. The initiator is decomposed by heating to generate free radicals, which initiate the free radical polymerization reaction of the first monomer and deposit a first polymer layer on the substrate surface. Stop the flow of the first monomer, and then vaporize the initiator and the second monomer by heating and let them flow into the reactor. The initiator decomposes by heating to generate free radicals, which initiate the free radical polymerization reaction of the second monomer, and deposit a second polymer layer on the surface of the first polymer layer. The difference in elastic modulus between the first polymer layer and the second polymer layer generates compressive stress during film growth, spontaneously forming a micro-nano wrinkled structure.
2. The method according to claim 1, characterized in that, The first monomer is 2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane, and the first polymer layer is poly(2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane); the second monomer is 1H,1H,2H,2H-perfluorodecyl acrylate, and the second polymer layer is poly(1H,1H,2H,2H-perfluorodecyl acrylate); Preferably, the initiator is di-tert-butyl peroxide, which is decomposed by heating with a nickel-chromium wire to generate free radicals.
3. The method according to claim 1, characterized in that, The thickness of the first polymer layer is 50 nm to 1000 nm; Preferably, the heating temperature of the nickel-chromium wire is 200°C to 400°C; Preferably, the temperature of the substrate during the deposition process is 30°C to 60°C; Preferably, the deposition reaction time of the second polymer layer is 1 to 20 minutes.
4. The method according to claim 1, characterized in that, The substrate is a rigid substrate or a substrate with a complex three-dimensional shape.
5. The method according to claim 1, characterized in that, The thickness of the first polymer layer is monitored by a real-time laser interferometer, and the inflow of the first monomer is stopped when the thickness reaches a predetermined value.
6. The method according to claim 1, characterized in that, The resulting film has a water contact angle greater than 150°.
7. The method according to claim 1, characterized in that, The micro-nano folded structure has a worm-like or labyrinthine morphology.
8. The method for preparing micro / nano wrinkles using polymer chemical vapor deposition technology according to claim 1, characterized in that, The initiator, the first functional monomer, and the second functional monomer are heated to (10-30)°C, (40-70)°C, and (60-90)°C, respectively.
9. A micro / nano wrinkled thin film, characterized in that, include: The first polymer layer is poly2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane; The second polymer layer is poly(1H,1H,2H,2H-perfluorodecyl acrylate); The first polymer layer and the second polymer layer are grafted to form a P(V3D3-g-PFDA) graft copolymer, and the film surface exhibits a micro-nano wrinkled morphology.
10. The application of the micro-nano pleats prepared by the method according to any one of claims 1 to 9 in anti-fouling, anti-frost, anti-icing, and antibacterial applications.